Colloidal BaZrS3 chalcogenide perovskite nanocrystals for thin film device fabrication. Issue 3 (13th January 2021) - Ravi, Vikash Kumar; Yu, Seong Hoon; Rajput, Parikshit Kumar; Nayak, Chandrani; Bhattacharyya, Dibyendu; Chung, Dae Sung; Nag, Angshuman
Abstract : Surface modification of BaZrS3 nanocrystals for colloidal dispersions and field effect transistors. A rare example of solution processed chalcogenide perovskite thin films. Abstract : The theoretical optoelectronic properties of chalcogenide perovskites ( e.g., BaZrS3 ) are as good as those of halide perovskites ( e.g., CH3 NH3 PbI3 ). But the fabrication of optoelectronic devices is rarely reported, mainly because researchers still do not know how to prepare good quality thin films of chalcogenide perovskites. Here, we report colloidal BaZrS3 nanocrystals (NCs, 40–60 nm) and their solution processed thin film transistors. BaZrS3 NCs are first prepared using a solid-state synthesis route, and the subsequent surface modifications lead to a colloidal dispersion of NCs in both polar N -methyl-2-pyrrolidinone and non-polar chloroform solvents. The NCs exhibit good thermal (15–673 K) and aqueous stability. Colloidal BaZrS3 NCs in chloroform are then used to make field effect transistors showing ambipolar properties with a hole mobility of 0.059 cm 2 V −1 s −1 and an electron mobility of 0.017 cm 2 V −1 s −1 . This report of solution processed chalcogenide perovskite thin films with reasonable carrier mobility and optical absorption and emission is expected to pave the way for future optoelectronic devices of chalcogenide perovskites.